Organizational Efficiency in Courts and Tribunals: An Unfinished Task/A Forgotten Task (London Journal of Research In Humanities and Social Sciences, 2025)
The purpose of this article is to address various issues related to the modernisation of the organisation of courts and tribunals in order to respond to the challenges of an increasingly complex and, at the same time, more demanding justice, to essential mechanisms to strengthen the effectiveness of judicial procedures as well as to the citizens guarantee regarding judicial claims. The likely implementation of a collegiate system in the first instance, which goes beyond the nineteenth century scheme of isolated courts which work as «kingdoms of taifas», re-opens with the presentation by the government of a draft for an Organization Efficiency Act, a project which is a mere replay of 2021 draft bill. If a broad political and professional consensus to promote the reform and its implementation is not to be reached, we might risk it that a modernization of justice will cease to be a pending issue and will turn into a forgotten subject.
Keywords: Human Rights; Cultural relativism; Human rights watch; Inherited; Male guardianship; Al Shafallah.; justice.; Justice Administration; Courts of First Instance; Court Organisation; Judicial Institution